Konstruksi Nalar Rechtvinding Hakim dalam Pemberian Izin Poligami yang Berkeadilan Gender dalam Putusan Pengadilan Agama Jombang No. 0899/Pdt.G/2016/PA.Jbg - Abdullah Taufik; Ilham Tohari (AL-HUKAMA, 2019)
The practice of polygamy in Indonesia until now has drawn criticism from some feminists who did not agree. But on the one hand, both Islamic law and positive law permit various conditions. In this case, the Religious Court (PA) becomes the last fence which becomes the determining point for a man to be able to polygamy. For this reason, researchers conducted a study of PA decisions on polygamy, namely Jombang PA Decision No. No. 0899 / Pdt.G / 2018 / PA.Jbg . The focus of the problem is (1) the value of gender justice in the decision and (2) reasoning rechtvinding(legal discovery) judge. The method used in this study is a normative-qualitative legal research method with content analysis techniques from Charles Purse. The results showed that the practice of polygamy licensing in the Religious Courts had actually gone through processes that reflected gender justice. This is reflected in the obligation of the Religious Court to summon the longest wife of the applicant for polygamy to be asked for willingness and information. The results of subsequent studies show that PA Jombang judges used hermeneutic techniques in making legal discovery efforts. Because, they not only focus on aspects of legality, but also consider the contextualization.